2013
DOI: 10.1016/j.biortech.2013.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Microbial utilization of aqueous co-products from hydrothermal liquefaction of microalgae Nannochloropsis oculata

Abstract: Hydrothermal liquefaction of algae biomass is a promising technology for the production of sustainable biofuels, but the non-oil, aqueous co-product of the process has only been examined to a limited extent. The aqueous phase from liquefaction of the alga Nannochloropsis oculata (AqAl) was used to make growth media for model heterotrophic microorganisms Escherichia coli, Pseudomonas putida, and Saccharomyces cerevisiae. Growth rates, yields, and carbon/nitrogen/phosphorus uptake were measured. E. coli and P. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 104 publications
(235 reference statements)
4
36
1
Order By: Relevance
“…Bacterial cultures have been verified to reduce the concentrations of these compounds in AP (Bajaj et al, 2008). For example, Nelson et al (2013) investigated the microbial utilization of AP from HTL of microalgae Nannochloropsis culata. They found that AP could be recycled via microbial cultures with significantly less dilution than previously published methods.…”
Section: Total Nitrogenmentioning
confidence: 99%
“…Bacterial cultures have been verified to reduce the concentrations of these compounds in AP (Bajaj et al, 2008). For example, Nelson et al (2013) investigated the microbial utilization of AP from HTL of microalgae Nannochloropsis culata. They found that AP could be recycled via microbial cultures with significantly less dilution than previously published methods.…”
Section: Total Nitrogenmentioning
confidence: 99%
“…Du et al [7] reused aqueous by-products from the hydrothermal carbonization process to cultivate C. vulgaris and reported that algae were growing much faster and producing more biomass than in the standard medium BG 11 at dilution ratios from 50 × to 200 ×. Nelson et al [8] showed that the aqueous phase obtained from HTL of Nannochloropsis occulata could be recycled for microbial growth of Escherichia coli and Pseudomonas putida at much lower dilution ratios than microalgae, demonstrating a higher tolerance of bacteria towards this by-product. García Alba et al [9] reported that 50% of the nutrients from the standard medium could be replaced by addition of the aqueous phase without compromising the growth of Desmodesmus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Savage, [10] reported yields from treating HTL-aqueous phase for kinetic parameters. Other studies have been mostly on recycling of aqueous phase to algae growth ponds, to cultivate algae biomass [11,12,13]. These reports have demonstrated feasibility of recovering additional yields from effluents and residues, however more research investigations on product recovery is necessary.…”
Section: Introductionmentioning
confidence: 99%